Response Surface Method for the Optimization of E. cloacae Strain UPM2021a Growth on Acrylamide as a Nitrogen Source (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
Acrylamide is often used in soil stabilization works. It is a neurotoxin and leachate from such stabilization works contaminate soils all around the world. E. cloacae strain UPM2021a which had been previously isolated and demonstrated the ability to degrade acrylamide was further studied for its critical parameters contributing to the optimum growth of acrylamide. The Box-Behnken design was utilized in optimizing the three previously identified significant components (pH, incubation time and acrylamide concentration). Of the three factors, acrylamide and pH were the significant factors. The response surface plot exhibited evidence of interactions. Predicted optimal conditions were determined using the "Numerical Optimisation" toolbox of the Design Expert software. Two optimal conditions were tested.  The model predicted a maximum growth of 10.686 (95% C.I., 10.458 to 10.913) which was verified through experimental results with a growth of 11.257 (95% C.I., 11.051 to 11.462) with the actual results being near to the predicted values but was significantly higher than the predicted values. The second numerical optimization gave a solution with a predicted maximum growth of 9.305 log CFU/mL (95% C.I. from 9.011 to 9.614) which was verified through experimental results with a growth of 9.978 log CFU/mL (95% C.I. from 9.830 to 10.126) with the actual results were also significantly higher than the predicted values. This means that other methods which employ more runs such as CCD or a different optimization approach such as Artificial Neural Network may be employed in the future to close the difference between the model predicted and actual experimental values. Despite this, the RSM exercise gave far better growth on acrylamide than OFAT with a higher response of about 2 log CFU/mL unit indicating the utility of RSM over OFAT in the optimization of growth of this bacterium on acrylamide.
Keywords: Acrylamide; Acrylamide-degrading bacterium; E. cloacae; RSM; Box-Behnken